Breathing Life into Sexuality Education: Becoming Sexual Subjects - Allen, Louisa (Philosophical Inquiry in Education, 2020)
This paper thinks with Todd’s (2017) ideas around ‘breathing life into education’ in relation to the curriculum area of sexuality education. It explores how this metaphor might be employed as a method for re-animating thought about the nature and purpose of sexuality education. The paper argues that sexuality education suffers from the stifling effects of instrumentalism and a neoliberal normativity that seeks to micro-manage the lives of students. Within sexuality education, this finds expression in a repetitive emphasis on reducing unplanned pregnancies and sexually transmissible infections. Confined by these foci, sexuality education’s pedagogical possibilities and transformative potential are limited. Breathing life into sexuality education offers opportunities for shaping this curriculum area as sensuous event. It also provides a life-enhancing pedagogical orientation that shifts focus from determining student’s imagined sexual futures, to attending to uncertainty in the present. Thinking with Todd’s ideas within the realm of sexuality education is an attempt to exercise their utility within a specific curriculum context. The paper also endeavours to press the metaphor of breath further, to characterise it as an act that is both mundane and profound. The implications of this conceptualisation for thinking about change in sexuality education are explored.